Design a questionnaire to measure the formation bilingual teacher of physical education (FBTPHED) - Zagalaz Sánchez, María Luisa; Molero López-Barajas, David; Cachón Zalagaz, Javier; Gutiérrez de Castro, Javier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2012)
The article gathers the design of an instrument to measure the opinion of the professorship of Physical Education (Ph.Ed.) in Primary Education (P.Ed.) on the bilingual education (English-Spanish) of his matter, that is to say, a questionnaire that allows to know if the professorship feels qualified to give EF's classes in English. The followed methodology is fitted inside the positivist paradigm by means of a descriptive study. The instrument object of study supposes a good approximation as measure. The questionnaire graduate applied himself to a sample of 40 subjects, all of them with the qualifications in Ph.Ed., later to proceed to the obtaining of the reliability of the before designed instrument. We calculate the coefficient alpha of Cronbach (1951) that was for the set of the questionnaire of 0.83. Nevertheless there are necessary more investigations that penetrate qualitatively to complement the results.